2004
DOI: 10.1002/jms.547
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the malondialdehyde–2′‐deoxyguanosine adduct in human urine by immuno‐extraction and liquid chromatography/atmospheric pressure chemical ionization tandem mass spectrometry

Abstract: The major adduct of malondialdehyde with guanine, M(1)G, was measured in human urine from non-smoking healthy individuals. M1G is a mutagenic DNA lesion and a terminal product of lipid peroxidation in vivo that may be implicated in cancer related to lifestyle and diet. On the basis of a recently developed method for the quantification of M1G as an excreted deoxynucleoside using immuno-extraction purification, chemical NaBH4 reduction and liquid chromatography combined with atmospheric pressure chemical ionizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 21 publications
0
55
0
Order By: Relevance
“…This may explain the reason that intracellular levels of M 1 dG are relatively insensitive to variations in plasma PUFA [33] although oxidation of PUFAs is known to give MDA and M 1 dG [33]. Furthermore, M 1 dG has been detected in urine samples at levels of 12+/-3.8 fmol kg -1 [35] and may also be oxidized to 6-oxo-M 1 dG adducts prior to excretion in urine [36,37]. It therefore appears that analysis of M 1 dG from blood DNA will not be a useful biomarker of colorectal cancer risk due to rapid excision and excretion and that the analysis of M 1 dG adducts in urine may prove to be more beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the reason that intracellular levels of M 1 dG are relatively insensitive to variations in plasma PUFA [33] although oxidation of PUFAs is known to give MDA and M 1 dG [33]. Furthermore, M 1 dG has been detected in urine samples at levels of 12+/-3.8 fmol kg -1 [35] and may also be oxidized to 6-oxo-M 1 dG adducts prior to excretion in urine [36,37]. It therefore appears that analysis of M 1 dG from blood DNA will not be a useful biomarker of colorectal cancer risk due to rapid excision and excretion and that the analysis of M 1 dG adducts in urine may prove to be more beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidized guanine adducts, 8-oxo-G and 8-oxo-dG, have been reported to be present in the urine of healthy human donors at levels of Ϸ2 nmol͞kg per 24 h and 0.4 nmol͞kg per 24 h, respectively (18). Attempts to quantify M 1 dG indicated that it is present at much lower concentrations in human urine, raising the possibility that it is metabolized before excretion (17).…”
Section: Discussionmentioning
confidence: 99%
“…We recently described a highly sensitive and specific method based on immunoaffinity purification and liquid chromatography (LC)-MS (16,17). Application of this technique reveals that M 1 dG is detectable in the urine of healthy human volunteers in amounts corresponding to 10-20 fmol͞kg per 24 h (17).…”
mentioning
confidence: 99%
“…M 1 -dG is reported to be a substrate for the nucleotide excision repair pathway (NER), which accounts for its appearance in human urine (13,20). This repair-dependent removal and subsequent deposition into urine provides an available source of M 1 dG for monitoring the exposure to oxidative damage (21).…”
Section: Introductionmentioning
confidence: 99%